Acute fatty liver disease of pregnancy-report of two cases from tertiary care centre, Hyderabad - Devabhaktuni, Pratibha; Malathi Ponnuru; Renuka Puli; Rajeshwari Jatoth; Kausalya Chakravarty (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
A referral case from Kollampally, Narayanpet, primi past EDD by 2 days, thrombocytopenia and elevated bilirubin levels. EDC-18.09.22, scan EDC- 26.09.22 She had a vaginal septum and a poor Bishop score. During caesarean section, there was atonic post-partum haemorrhage, (PPH). When PPH could not be controlled with medical management, Haymans stitches were applied to control the bleeding. Total she received seventeen units of blood products, (4 FFPS, 1 SDP, 2 PRBC, 10 CRYO). She succumbed on the fourth POD. Fulminant hepatic failure, hepatic encephalopathy, grade 111, oliguric, AKI, thrombocytopenia, coagulopathy, with sepsis. The second case, a 24 years primi, 38 weeks 4 days, jaundice of three days duration, with HELLP? AFLP, thrombocytopenia with poor Bishop score. This case was a referral from SVS medical college, Mahaboob Nagar (MBNR) on 25.10.22, 7.23pm. An emergency LSCS was performed on 26.10. 22, 2.15 am. Blood products 25 units, (1 PRBC, 8 FFP, 6 RDP, 10 Cryo) units transfused. Intra operative blood loss was 1250 ml. Atonic PPH was managed adopting both medical and surgical, methods. An alive male 3200 gm was delivered. Measures taken to control PPH were, misoprostol 800 mcg PR, inj.oxytocin 20 units i.v drip, uterine massage, Inj. Carboprost was given. Modified B Lynch uterine compression sutures were applied. Bilateral uterine artery ligation was done. Abdominal drain kept. AKI, sepsis and increasing bilirubin levels were noted. At OGH two sessions of haemodialysis were done. Patient expired on 28.10.22. Persistent hypoglycemia, elevated bilirubin, low fibrinogen, prolonged PT and INR pointed to a diagnosis of AFLP.